Proceedings of the 2012 International Conference on Quantitative InfraRed Thermography 2012
DOI: 10.21611/qirt.2012.276
|View full text |Cite
|
Sign up to set email alerts
|

Thermal signature of melanoma and non-melanoma skin cancers

Abstract: In this work the thermal signature of melanoma and non-melanoma skin cancers is investigated in order to be used as a non-invasive aid in the diagnosis and the vascular assessment of these types of skin cancers. Thirty patients with melanoma and non-melanoma skin cancers were examined in order to obtain their temperature profile. The results show that there is a characteristic thermal signature for different types of skin neoplasms which not necessarily depend exclusively on their vascularity. Basal cell carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Angiogenesis is the physiological process by which new blood vessels form from existing vessels to provide the necessary extra energy [45][46][47]. In conjunction with the increased energy requirements, melanoma skin lesions are thought to have a higher (∆ 2-4 K) temperature than the surrounding healthy skin [27,[48][49][50]. Therefore, IR imaging for melanoma skin lesions is based on the detection of new blood vessels and chemical changes associated with a tumour development and growth [42,51].…”
Section: Skin Cancer and Infrared Thermographymentioning
confidence: 99%
See 1 more Smart Citation
“…Angiogenesis is the physiological process by which new blood vessels form from existing vessels to provide the necessary extra energy [45][46][47]. In conjunction with the increased energy requirements, melanoma skin lesions are thought to have a higher (∆ 2-4 K) temperature than the surrounding healthy skin [27,[48][49][50]. Therefore, IR imaging for melanoma skin lesions is based on the detection of new blood vessels and chemical changes associated with a tumour development and growth [42,51].…”
Section: Skin Cancer and Infrared Thermographymentioning
confidence: 99%
“…Other skin tumor types, such as basal cell carcinoma may form an encapsulating layer of involved cells which acts like a thermal insulator, resulting in a delayed thermoregulatory process [27,52]. Similarly, González et al [50] studied the vascularity of different skin lesions (melanoma and non-melanoma) and discovered that each cancer type has its own thermal signature.…”
Section: Skin Cancer and Infrared Thermographymentioning
confidence: 99%
“…Thermal imaging (66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77) is the leading technique investigated in literature. Thermal cameras were used to obtain skin lesion features at steady-state (71,74,77) and in dynamic thermal conditions (66)(67)(68)(69)(70)(72)(73)(74)(75)(76)(77). In steady-state studies, thermal images were used to obtain temperature features of the investigated lesion, such as, pixels temperature profiles (74) and temperature difference between several type of lesions and the healthy surrounding skin (71).…”
Section: Thermal Measurementsmentioning
confidence: 99%
“…Thermal cameras were used to obtain skin lesion features at steady-state (71,74,77) and in dynamic thermal conditions (66)(67)(68)(69)(70)(72)(73)(74)(75)(76)(77). In steady-state studies, thermal images were used to obtain temperature features of the investigated lesion, such as, pixels temperature profiles (74) and temperature difference between several type of lesions and the healthy surrounding skin (71). Some authors suggested that the application of a cooling stress is essential to highlight malignancy: indeed, the thermal recovery of the lesion over time differs between malignant and benign tissues.…”
Section: Thermal Measurementsmentioning
confidence: 99%
“…They tested their setup in 37 patients, achieving better results than using conventional diagnostic techniques [34]. Similarly, González et al [35] studied the vascularity of skin lesions and concluded that there is a characteristic thermal signature associated with each type of cancer. In previous work [36], [37], we presented a set of algorithms to detect cancerous skin lesions using the TRCs of the suspicious lesion and its surrounding tissue, measured after cooling.…”
Section: Introductionmentioning
confidence: 99%